ANALYSIS OF THE PROFILE OF PATIENTS WITH ORAL CAVITY NEOPLASIA - Isabella Souza Santos, Lara; de Oliveira Alves, Geiza; de Souza Ferreira, Lorena; Palmeira Eleutério, Cynthia; do Nascimento Chaves Lima, Alex; Dias, Graziela; Alves Soares, Juliana; Ferreira de Carvalho Alves, Cândida; de Souza Ramos, Dayara; de Andrade Huber, Lucas; Rúbia Rockenbach, Ana; Elson Amaral dos Santos, José; et al. (Health and Society, 2024)
Objective: To describe the profile of patients with oral cavity cancer from 2015 to 2019 in Montes Claros, Minas Gerais State, Brazil. Methods: this is a descriptive study with a quantitative approach using data from patients living in Montes Claros, Minas Gerais, Brazil, diagnosed with oral cavity neoplasia in the hospital records of the José Alencar Gomes da Silva National Cancer Institute (INCA). Results and discussion: In the historical series analyzed, 312 cases of oral cavity neoplasia were identified among patients living in the analyzed region. Conclusion: the patients who were diagnosed with oral cavity cancer were mostly men aged between 50 and 69 years, and the association between the concomitant use of tobacco and alcoholic beverages was present in the vast majority of cases. Efforts are needed by health professionals and managers for early diagnosis through educational and primary prevention actions.